2013
DOI: 10.1371/journal.pone.0078344
|View full text |Cite
|
Sign up to set email alerts
|

MiR-200c Increases the Radiosensitivity of Non-Small-Cell Lung Cancer Cell Line A549 by Targeting VEGF-VEGFR2 Pathway

Abstract: MicroRNAs (miRNAs) have been demonstrated to participate in many important cellular processes including radiosensitization. VEGF family, an important regulator of angiogenesis, also plays a crucial role in the regulation of cancer cell radiosensitivity. VEGFR2 mediates the major growth and permeability actions of VEGF in a paracrine/autocrine manner. MiR-200c, at the nexus of epithelial-mesenchymal transition (EMT), is predicted to target VEGFR2. The purpose of this study is to test the hypothesis that regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 18 publications
5
53
0
Order By: Relevance
“…miR-200c directly targets many pro-inflammatory genes, including IL-8, VEGFA, and VEGFR2. Additionally, miR-200c also targets IKK␤ (IKBKB), thereby decreasing Nf-B signaling and inhibiting scores of pro-inflammatory Nf-B-target genes (51)(52)(53). Furthermore, as let-7d, miR-23b, and miR200c are established tumor suppressor genes that are significantly down-regulated in OSCC, our data provide a potential mechanism whereby PAR-2 activation contributes to tumor progression (54 -61).…”
Section: Par-2-mediated Nf-b Activation Suppresses Micrornamentioning
confidence: 79%
“…miR-200c directly targets many pro-inflammatory genes, including IL-8, VEGFA, and VEGFR2. Additionally, miR-200c also targets IKK␤ (IKBKB), thereby decreasing Nf-B signaling and inhibiting scores of pro-inflammatory Nf-B-target genes (51)(52)(53). Furthermore, as let-7d, miR-23b, and miR200c are established tumor suppressor genes that are significantly down-regulated in OSCC, our data provide a potential mechanism whereby PAR-2 activation contributes to tumor progression (54 -61).…”
Section: Par-2-mediated Nf-b Activation Suppresses Micrornamentioning
confidence: 79%
“…Recently, emerging evidence reported that dysregulation of miRNAs may contribute to tumor development [18,19]. miRNAs, small noncoding RNAs, could regulate expression of the proteincoding genes [20][21][22]. It is already identified that miRNAs are related to cell apoptosis, prognosis, proliferation, and invasion [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The major causes of death from cancer are complications arising from metastasis. microRNAs (miRNAs) have been reported to have critical regulatory roles in cancer biology [16,17,18]. Specifically for EC, it is already reported that miRNAs contributes to proliferation and invasion [19,20].…”
Section: Discussionmentioning
confidence: 99%